Factors associated with urinary lithiasis detected by ultrasound and radiography at the Cinquantenaire Hospital of Kisangani - BAMBALE LIMENGO, Jean-Paul; AHUKA LONGOMBE, Lambert; MAZOBA KPANYA, Tacite; KAKULE LWANGA, Lwanga; MBONGO TANZIA, Angèle; FALAY SADIKI, Dadi; TAGOTO TEPUNGIPAME, Alliance; BISUTA FUEZA, Serge; KAYEMBE TSHILUMBA, Charles; MOLUA AUNDU, Antoine (Orapuh Journal, 2026)
Introduction Urinary lithiasis is an increasingly significant public health concern in sub-Saharan Africa. However, in the Democratic Republic of the Congo (DRC), epidemiological data and factors associated with this condition remain limited. Purpose This study aimed to analyze factors associated with urinary lithiasis among patients examined in Kisangani. Methods A cross-sectional analytical study was conducted involving 303 patients who underwent ultrasound and/or radiography for suspected urinary lithiasis at the Cinquantenaire Hospital of Kisangani between 2020 and 2024. Qualitative variables were expressed as proportions, while age was presented as mean ± standard deviation. Bivariate analysis was performed to identify significant associations using Pearson’s chi-square test or Fisher’s exact test at a 5% significance level. Crude odds ratios (ORs) with 95% confidence intervals (CIs) and Wald p-values were calculated. Results The mean age of the patients was 41.9 ± 15.3 years, with a predominance of individuals aged 30 to 49 years. Bivariate analysis revealed a statistically significant association between urinary lithiasis and a personal history of lithiasis (crude OR = 3.43, p = .030), as well as the presence of a urinary tract infection (crude OR = 2.45, p = .012). Conclusion Young adulthood, a history of kidney stones, and urinary tract infection appear to be significantly associated factors. These findings highlight the need to strengthen targeted ultrasound screening and to integrate the management of risk factors into local public health strategies.